2017
DOI: 10.18388/abp.2016_1454
|View full text |Cite
|
Sign up to set email alerts
|

The influence of CSN3 and LGB polymorphisms on milk production and chemical composition in Romanian Simmental cattle

Abstract: The aim of this study was to assess the influence of genotypes from the CSN3 and LGB loci on milk production and chemical composition in Romanian Simmental cattle (n=114). For the CSN3 locus a significantly higher frequency (P≤0.001) was observed for the allele A (0.785) compared to allele B (0.215) and for AA (0.631) compared to AB (0.307) and BB (0.062) genotypes, respectively. The AA genotype was associated with a higher milk production (5887.76±115.7 kg) compared to the yields associated with the BB genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 14 publications
3
16
0
3
Order By: Relevance
“…In fact, identical results for Czech Simmental cattle were reported by Kučerová et al (2006) and Bartoňová et al 2012). Neamt et al (2017) discovered the marked predominance of the A allele (0.785) above the B allele (0.215). Research of Trakovická et al, 2012) reported similar results.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…In fact, identical results for Czech Simmental cattle were reported by Kučerová et al (2006) and Bartoňová et al 2012). Neamt et al (2017) discovered the marked predominance of the A allele (0.785) above the B allele (0.215). Research of Trakovická et al, 2012) reported similar results.…”
Section: Resultssupporting
confidence: 78%
“…The same genotype order was also described in Holstein crossbred cows in the study of Molee et al (2015), AB 0.535, BB 0.289 and AA 0.175. The AB genotype was discovered to be the most frequent also in the study of Neamt et al (2017). The LGB gene was the only gene included in our analysis not to be in HWE.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Czerniawska-Piatkowska et al (2011) found that cows with the LGB AA genotype were characterized by the highest milk yield in all lactations and cows with the LGB BB genotype was associated with the highest milk fat yield and content for the three lactations. Neamt et al (2017) reported that the AB genotype was associated with a higher milk production and the BB genotype was associated with a higher fat percentage in milk compared with the other two genotypes. Neither did Litwinczuk et al (2003) and Micinski et al (2008) find any association between LGB genotypes and milk production traits.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%